F.l.t.r. at the table: journalists, Taşkin (TEKSIF, head of Aydin branch), Erdem (TEKSIF), Gürmeriç (Türk-Iş) and branch executive committee members
F.l.t.r. at the table: journalists, Taşkin (TEKSIF, head of Aydin branch), Erdem (TEKSIF), Gürmeriç (Türk-Iş) and branch executive committee members.